Implementasi Pendidikan Kecakapan Hidup di Mi Ma’arif NU I Klapagading Kecamatan Wangon Kabupaten Banyumas - Qurotul Aini Farida (LPPM IAINU Kebumen, 2019)
Life-skills education is an educational model that builds hard skills and soft skills in an integrated manner. Strengthening students' soft skills will strengthen their hard skills and vice versa. People with character are people who are able to balance soft skills and hard skills in acting and behaving in society. Implementation of life skills education personal skills in learning a. Self-esteem as a creature of God Almighty. including: 1) Saying greetings when meeting teachers and friends 2) Shaking hands or shaking hands when coming to and from school 3) Praying before and after learning activities 4) Reading Asmaul Husna every day 5) Memorizing short letters (Juz Amma) and Tahfidz 6) Memorization of daily prayers and hadiths and their meanings 7) Dhuha prayer 8) Duhur prayer in congregation. b) Independent namely 1) Morning call and 2) Romadhon Pondok. Implementation of social skills life skills education a) Oral or written communication skills. b) Cooperation skills, namely 1) Scouting and 2) group assignments. Implementation of academic skills life skills education, namely effective and fun learning programs and Teacher Learning Management. Implementation of vocational skills life skills education in learning includes performing ablution, learning prayer movements, putting on and taking off one's own clothes, sweeping floors and tidying up classrooms, playing roles, reading poetry, composing short stories. and Planting vegetables such as kale, spinach and pokcai.